2015
DOI: 10.1002/jib.286
|View full text |Cite
|
Sign up to set email alerts
|

Study on the buffering capacity of wort

Abstract: The effect of the buffering capacity of wort on a beer fermentation and the contribution of pH, phosphate, amino acids and organic acids to the buffering capacity of wort were studied. The beer pH depended on the buffering capacity of the corresponding wort and an increase in the buffering capacity of the wort could prolong the time of diacetyl conversion. The higher the wort pH was, the larger the wort buffering capacity. Phosphate was not an effective buffer at the pH of wort. Glutamic acid, aspartic acid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…For relatively simple defined solutions of weak acids or bases, buffering may be modeled analytically to determine pH, the concentrations of all the ions in solution, as well as uncharged acid or base species. For undefined systems with multiple unknown buffers, the BC can be estimated using the derivative of titration curves for environmental applications such as landfill leachate (Gibs, Shoenberger, & Suffet, 1982), water quality (Van Vooren, Van De Steene, Ottoy, & Vanrolleghem, 2001), and beverages including beer and wine (Dartiguenave, Jeandet, & Maujean, 2000; Li, Liu, Kang, & Zheng, 2015). Estimating the p K and concentration of buffers in solution requires numerical methods for nonlinear curve fitting.…”
Section: Introductionmentioning
confidence: 99%
“…For relatively simple defined solutions of weak acids or bases, buffering may be modeled analytically to determine pH, the concentrations of all the ions in solution, as well as uncharged acid or base species. For undefined systems with multiple unknown buffers, the BC can be estimated using the derivative of titration curves for environmental applications such as landfill leachate (Gibs, Shoenberger, & Suffet, 1982), water quality (Van Vooren, Van De Steene, Ottoy, & Vanrolleghem, 2001), and beverages including beer and wine (Dartiguenave, Jeandet, & Maujean, 2000; Li, Liu, Kang, & Zheng, 2015). Estimating the p K and concentration of buffers in solution requires numerical methods for nonlinear curve fitting.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, BC has been investigated as an important factor influencing beer fermentations (Li, Liu, Kang, & Zheng, ), fermentation disorders in ruminant animals (Hille et al., ) water quality (Van Vooren, Van De Steene, Ottoy, & Vanrolleghem, ), and the BC of whey in cheese‐making (Hill, Irvine, & Bullock, ). However, the use of BC to estimate the pH of food ingredient mixtures or determine the influence food ingredients on equilibrium pH of acid or acidified foods has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…Both nitrogenous compounds (amino acids and peptides) and phosphates have long been considered as the most important buffering substances in wort . However, a recent study by Li et al questioned the relevant contribution of both free amino acids and phosphates to the overall BC. The authors concluded that, because of the very low or very high p K a values of the α ‐carboxylic acid group (range 1.7–2.2) or α ‐amino group (range 8.8–10.6), respectively, most amino acids contribute only poorly to the BC in the relevant pH range for lactic fermentation .…”
Section: Discussionmentioning
confidence: 99%